Identifikasi Miskonsepsi Siswa SD Negeri Panggang Menggunakan Tes Diagnostik Two-Tier Pada Materi Wujud Zat Dan Perubahannya - Qatrunnada, Assita Azka; Purnomo, Heru; Kurniawati, Wahyu (Pendagogia: Jurnal Pendidikan Dasar, 2025)
At the elementary school level, education has a very important role in shaping the way students think and providing a strong foundation for understanding various basic concepts in science. However, in reality there are still many students who experience misconceptions. This study aims to identify students' misconceptions through a two-tier diagnostic test. The diagnostic test consisted of 25 multiple choice items covering three subconcepts and was tested on 51 fourth grade students. The research method used is descriptive qualitative method because this research only focuses on one variable, namely student misconceptions that occur in learning the topic of the form of substances and their changes. The test results show that students' misconceptions are quite high, namely 61.43% with the highest misconception topic on the types of substances, which is 70%. Based on these results, it can be concluded that diagnostic tests need to be carried out in learning to be able to reveal students' misconceptions before learning.